A Materialist Study of Canadian Literary Culture at a Time of Neoliberal Globalization - Milz, Sabine (My University, 2004)
In this dissertation I query a notion that is prevalent among contemporary literary critics, cultural policy-makers, and media representatives in Canada: the notion that Canadian literature is national "soul-stuff" and thus not an ordinary commodity. I argue that this notion obscures the crucial nexuses at which the literary, economic, and political spheres blur inside Canada. My analysis of Canada's literary conditions under contemporary globalization examines just these nexuses. It pries apart the discourses of national literature and national identity in order to investigate how they function and onto which economic, political, and social values they project themselves. With this approach, I do not intimate that Canadian literature does not have any non-market value. Rather, I want to draw attention to the fact that the traditional focus on literature as a trope of non-material, national values masks what is really at stake at the present moment -namely questions of "value." What are the social and political values that structure contemporary Canadian society: its political organization, public sphere, cultural production, public policies? How are literary-cultural decisions made and by whom? These questions open to scrutiny nationalist narratives of globalization, which tend to reduce contemporary processes of globalization (such as global cultural commodification) to the totalizing force of U.S. neo-imperialism. Not only is Canada's relationship to cultural imperialism, capitalism, and globalizing forces more complicated than assumed in such reasoning, but globalization also is a more complicated phenomenon than the currently widespread notion of U.S. neo-imperialism suggests. I show that this notion has in substantial ways distracted from the active and voluntary involvement of other parties and countries in the current neoliberal restructuring of global power, which asserts as inevitable the commercialization and privatization of cultural and social goods, policies, and public functions, and the deregulation of markets. In Canada, claims of cultural-national sovereignty and strategies of cultural protection have tended to omit the fact that the increasing conversion of Canada's "national literature" in economic terms is symptom of this neoliberal restructuring process in which the Canadian government actively participates by depoliticizing its functions and handing control over markets to multinational corporations, international trade agreements, and international judicial and political instruments. Subsequently, I propose that we should not, at this point, study (and teach) Canadian literature in order to protect a national tradition and assert the image of an autonomous literature of multicultural "Canadianness," but in order to approach the question of globalization and the issue of neoliberalism from alternative perspectives. Hence, I also distance myself from postmodernist approaches to the literary study of globalization, which tend to read the latter in purely textual terms that emphasize transnational and transcultural images and narratives. While this postmodernist focus has in many ways countered the totalizing implications of the term globalization, it has run the risk of excluding the material realities of literary globalization from its inventory of study objects. So has the more recent North American discourse of "global literary study," which has been largely limited to postmodernist idealizations and transnational histories of globalization. As an alternative to these readings, I propose a materialist literary approach that emphasizes that an understanding of the contemporary literary conditions in Canada requires an understanding of neoliberal globalization as the context within which literary studies articulates itself as an academic discipline and within which the production and consumption of literature takes place today. Materialist literary criticism engages in a process of critical interdisciplinarity -at the junction of the fields of English-Canadian literary studies, cultural studies, postcolonial studies, and globalization studies -that is non-nationalist and unsettling of the neoliberal power structures and values that increasingly pervade universities and cultural policies and markets. The dissertation chapters explore the possibility and emphasize the actual existence of alternative globalization processes and narratives. The first chapter does so by engaging in the more recent North American debate on the literary study of globalization. The second chapter discusses the neoliberal orientation in the present practice of modernrepresentative democracy in Canada in order to test the grounds for alternative methods of more inclusive cultural decision-making, especially as it relates to literary production. In opposition to the still-prevalent modernist ideal-purported most notably by Northrop Frye and A.J .M. Smith -of a globally vanguardist Canadian literature, the study of Aboriginal and ethnic minority writers undertaken in the third chapter brings forth an "allochronic" (or differently-timed) understanding of Canadian literature, globalization, and their interrelations. The fourth chapter complicates the cultural nationalist binary of Canadian-owned, government-funded publishing and foreign-owned, market-driven publishing. It explores the idea of alternative publishing by means of interviews with small-scale Aboriginal and EuroCanadian publishers and an analysis of radical Canadian writers that publish with big publishing conglomerates such as Random House and HarperCollins.
Keywords: Canadian Literary; Globalization